Perilaku Pemilih Di Gampong: Dinamika Demokrasi Tingkat Lokal dan Faktor-Faktor Penentu - Dewi, Mellita; Chadijah, Devi Intan; Lestari, Yeni Sri (Jurnal PUBLIQUE, 2026)
This study begins with voter behavior in the village head election in Gunong Kleng Village, highlighting the dynamics of democracy at the village or local level and its determining factors, such as money politics and kinship. Academic concerns have arisen due to the practice of money politics and kinship, which violate the principles of honest and fair democracy and have the potential to erode the integrity and quality of village leadership. This study used a qualitative approach with data collection techniques such as observation, interviews, documentation, and validity tested by triangulation of methods and sources. The research findings show that voter behavior is still strongly influenced by these two factors, resulting in the democratic process at the village level being less than ideal and more dominated by the interests of certain groups or individuals. This indicates the need for political education and stricter and more transparent supervision to create honest and rational voters.